the THE EFFECT OF CHITOSAN COATING ON MAFENIDE ACETATE-LOADED LIPOSOME CHARACTERIZATION AND DELIVERY THROUGH BURNED RAT SKIN - BEHZAD SHARIF MAKHMAL ZADEH; BAHAREH KHANDEH ZAMIN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Mafenide acetate has appropriate antibacterial activity against Gram-positive bacteria isolated from the eschar surface. This drug has a high permeability through eschar which causes not only low concentration in the target place but also systemic toxicity. The aim of this study was localization of mafenide acetate into the eschar by chitosome. Methods: In this study, liposomes are prepared with thin-layer hydration method and then covered by chitosan film. Based on full factorial design, different formulation was prepared and characterized and the selected formulation was applied on burned rat skin. Results: Chitosan decreased membrane fluidity by interaction with phospholipid and cholesterol that induced lower drug loading efficiency and higher particle size of chitosomal formulation in comparison with liposomal formulations. Mucoadhesive and slow drug release property of chitosomes provided higher drug concentration into the eschar. Conclusion: Impairment barrier property of eschar can be treated by the application of chitosomes. Chitosomes provided more drug concentration into the eschar and so are better vehicles for burn wound treatment in comparison with liposomes.